The technology toolbelt for teaching - Manning, Susan, 1960-; Johnson, Kevin E. (San Francisco : Jossey-Bass, 2011)
"Instructors are pressured to integrate technology into their traditional or online instruction. This book offers a hands-on resource that shows how to integrate technology into lessons and offers information about common technologies, categorizing by groups, and explains the purposes they serve pedagogically as well as how they can be most effectively used in online or face-to-face classrooms. In addition to examples, each chapter will feature a decision making matrix to help instructors decide on whether or not a tool is really needed based on curriculum objectives or a specific organizational or curricular problem."--
pt. 1: Introduction. Why Web-based tools? -- How to choose tools and a matrix for doing so -- pt. 2: Tools to help you stay organized. Calendars -- Scheduling tools -- Mind-mapping or graphic organizer tools -- Social bookmarking -- Virtual storage and file management -- pt. 3: Tools to communicate and collaborate. Discussion forums -- Voice Over Internet Protocol -- Instant messaging and chat -- Blogs -- Wikis -- Microblogs -- Web conferencing -- pt. 4: Tools to present content. Audio -- Video -- Screencasting -- Narrated slide shows -- Sharing images -- pt. 5: Tools to help you assess learning. Quizzes, tests, and surveys -- Rubrics and matrixes -- E-portfolios -- pt. 6: Tools to help you transform your identity. Avatars -- Virtual worlds -- Social networking and your students' identities -- Emerging technology.
Includes bibliographical references (p. 199-201) and index.
Keywords: Educational technology; Computer-assisted instruction; EDUCATION / General